2014
DOI: 10.1016/j.rehab.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Interlimb neural coupling: Implications for poststroke hemiparesis

Abstract: Interlimb coordination is essential to perform goal-directed daily tasks and purposeful locomotion. The coordination occurs due to spatiotemporal coupling of movements, which also comprises interactions in segmental kinematics, joint dynamics, and muscle activity. Neuroanatomical and neurophysiological linkages at the spinal and brain level are responsible for the coordination. The linkage is termed "neural coupling". According to the task demand, the coupling may occur between two upper limbs or two lower lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 103 publications
(309 reference statements)
3
41
0
Order By: Relevance
“…Both in-phase and antiphase movements require synchronization between the two sides of the upper limbs, but the antiphase movements additionally need contralateral movement suppression and the independence of the two movements [35]. There is an interhemispheric synchronization and disinhibition to control the coupled bimanual upper limb movement [4]. These studies [10, 56, 57] showed that the CMA suppresses the intrinsically favored coordination tendencies and facilitates less familiar bimanual movements; because of that, the CMA appears to play a more generic role related to cognitive control and response inhibition [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both in-phase and antiphase movements require synchronization between the two sides of the upper limbs, but the antiphase movements additionally need contralateral movement suppression and the independence of the two movements [35]. There is an interhemispheric synchronization and disinhibition to control the coupled bimanual upper limb movement [4]. These studies [10, 56, 57] showed that the CMA suppresses the intrinsically favored coordination tendencies and facilitates less familiar bimanual movements; because of that, the CMA appears to play a more generic role related to cognitive control and response inhibition [34].…”
Section: Discussionmentioning
confidence: 99%
“…Most daily movements require certain degree of collaboration between the upper limbs [13]; interlimb coordination is important for performing goal-oriented daily movements [4]. Bimanual movements, which are more abundant than unimanual movements [3], are effective instruments to investigate motor dysfunctions in general and the underlining mechanisms of asymmetry and lateralization following neurodegenerative disorders and other neurological diseases [3, 5, 6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coordination is closely correlated with the degrees of motor recovery and rehabilitation27 ) . Adequate coordination of the lower limbs is essential for performing daily tasks and purposeful locomotion28 ) . Therefore, enhancing the coordination of the lower limb may improve post-stroke outcomes29 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In the context of hemiparetic gait rehabilitation, the study of interlimb coordination mechanisms might be of great significance. In fact, it has been shown that neural coupling exists in poststroke patients as it does in healthy subjects (Arya and Pandian, 2014) and for the upper limbs as well (Yoon et al, 2010). In studies with poststroke subjects with hemiparesis, it was found that neural decoupling between the lower limbs perturbs the paretic lower limb function (Kautz and Patten, 2005).…”
Section: Inter-limb Coordination Mechanismsmentioning
confidence: 99%